The Death of Traditional Advertising: How the Rise of Digital Marketing is Changing the Way We Reach Customers - Risdwiyanto, Andriya (Penelitian dan Pengembangan Ilmu, 2024)
In the context of the evolution of advertising from traditional to digital, this research aims to identify the main factors influencing this shift and its impact on consumer behavior. The research method used is a systematic literature review by collecting articles from reputable international databases such as Scopus, PubMed, and Web of Science. The results of the discussion show that this advertising transformation is driven by technological advances, demographic changes, social and cultural changes, economic changes, as well as related regulations and policies. The implication of this research is to provide new insights for business practitioners and academics in facing the challenges of advertising transformation in this digital era. Some limitations of this research include a focus primarily on factors influencing the shift to digital marketing, limitations in the time scope of the research, and the possibility that relevant research is inaccessible. Implications for future research are to expand the scope of research to include other factors influencing advertising shifts, use a more diversified methodological approach, and compare traditional and digital advertising practices in various geographic contexts.